Impact of anchorage miniscrews in multibracket treatments without extractions. (30th September 2014) - Baron, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Over the past decade, the interest for miniscrews is continuously growing as confirmed by the amount of recent published studies. In particular, their use allows to make corrections in a single phase and avoids extractions of premolars, while keeping usual goals of treatment. Main results of pilot studies and some clinical examples are presented here to illustrate our therapeutic approach for the treatment of tooth discrepancy in Class I, Class II and Class III situations.